2010
DOI: 10.1080/13557851003728264
|View full text |Cite
|
Sign up to set email alerts
|

Culture and sex education: the acquisition of sexual knowledge for a group of Vietnamese Australian young women

Abstract: It is imperative for young people to have adequate and appropriate sexual education so that informed and safe sexual choices can be made. For young people from diverse cultural backgrounds, this education must be culturally appropriate and accessible, taking into consideration cultural mores regarding gender and sexual matters, as well as current beliefs in the 'mainstream' youth culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 47 publications
3
74
1
1
Order By: Relevance
“…This aversion also may be due to sociocultural reasons. Workers in other parts of Nigeria (Izugbara, 2005;Iyaniwura, 2006), Africa (Mckay & Holowaty, 1997) and elsewhere (Rawson & Liamputtong, 2010) reported that parents infrequently deal with practical issues (such as how to obtain or use contraceptives, or with psychological or experiential aspects of sexuality such as sexual decision-making). Although our teenage respondents were less forthcoming over the areas of sexuality and reproductive health and wish to have more information from their mothers, their peers in the developed countries suggested that parents need to supplement the more routinely covered topics of physical development and reproduction to deal with positive aspects of sexuality, such as commitments and emotional factors, dating and boyfriends, and practical issues such as contraception and prevention of STIs (Walker, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…This aversion also may be due to sociocultural reasons. Workers in other parts of Nigeria (Izugbara, 2005;Iyaniwura, 2006), Africa (Mckay & Holowaty, 1997) and elsewhere (Rawson & Liamputtong, 2010) reported that parents infrequently deal with practical issues (such as how to obtain or use contraceptives, or with psychological or experiential aspects of sexuality such as sexual decision-making). Although our teenage respondents were less forthcoming over the areas of sexuality and reproductive health and wish to have more information from their mothers, their peers in the developed countries suggested that parents need to supplement the more routinely covered topics of physical development and reproduction to deal with positive aspects of sexuality, such as commitments and emotional factors, dating and boyfriends, and practical issues such as contraception and prevention of STIs (Walker, 2001).…”
Section: Discussionmentioning
confidence: 97%
“…Some previous research in Australia considered migrants as a homogeneous group which makes understanding SRH differences within and among cultures difficult [46]. However, HCP’s perceive that refugee and migrant women’s SRH knowledge and engagement with care varied with their individual level factors such as age, country of origin, length of stay in Australia and educational status.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this was not the case. Information on contraception should come from parents or teachers, but research has identified that this is not often the case (Rawson & Liamputtong 2010).…”
Section: Discussionmentioning
confidence: 99%